(untitled) (Altre Modernità, 2017)
In mainstream Second Language Acquisition (SLA), errors are viewed as indicators of learners’ interlanguage development and of the mental processes involved. While there is considerable variation regarding how errors are treated in classroom contexts, research has shown what type of corrective strategies can be most beneficial in helping learners notice their errors and providing them with opportunities for language acquisition. In this paper, I intend to focus on oral corrective feedback. I first consider how it is both handled in language pedagogy and investigated in second language research. Next, I present an observational study that aimed to explore teacher corrective feedback strategies in four Italian "English as a Foreign Language (EFL)" classrooms. Selected data from classroom observation are analysed vis-à-vis teachers’ beliefs about their use of corrective feedback. Finally, implications of corrective feedback research for teacher education are highlighted.